The pulmonary physician in critical care 5: Acute lung injury and the acute respiratory distress syndrome: definitions and epidemiology. Issue 5 (1st May 2002) - Atabai, K; Matthay, M A
Abstract : An understanding of the epidemiology of ALI/ARDS and the effects of treatment have been hampered by the lack of a uniform definition of the syndrome. Various definitions have been proposed, and these are reviewed with particular attention to how changes in definition have affected our understanding of the natural history and treatment options for the condition.